Overseed timing of ryegrass and cereal rye in soybean affects rotational crops in upstate Missouri. Issue 2 (8th August 2022) - Nelson, Kelly A.; Belknap, Renee A.; Brake, Derek; Singh, Gurbir
Abstract: Overseeding may help farmers establish cover crops (CCs) in a relay intercropping system and avoid labor and time constraints during harvest while providing grazing opportunities for integrated crop–livestock systems. This research evaluated timings (overseeded at R6, R6.5, R7, R8, and post‐harvest) of cereal rye (CR; Secale cereale L.) and ryegrass (RG; Lolium multiflorum L.) CC plantings on soybean [ Glycine max (L.) Merr.] yield, CC heights and dry mass in the spring, and the subsequent impact on rotational crop (corn [ Zea mays L.] or soybean) yield compared with the absence of a CC (nonseeded control) and drill‐seeded CC treatments following soybean harvest. Soybean light interception (LI) during the overseeding timings differed between years which along with precipitation and temperature affected fall and spring growth of grass CCs. Earlier‐seeded CCs were generally taller and had greater dry mass than post‐harvest seedings, depending on the year. Conventional‐tilled soybean yields and the subsequent no‐till soybean crop following CCs were not affected when CCs were seeded at R6.5 or later. No‐till soybean yields were not affected by overseeded CCs when seeded at R6 or later; however, all CC seedings except post‐harvest overseeded CCs reduced corn yields 16–33 bu acre –1 compared with the nonseeded control. Overseeding is an option for farmers wanting to establish a CC, but risk to the intercropped and rotational crop yield occurs if seeded too early and can depend on the rotational crop. Core Ideas: Light interception by the soybean crop affected cover crop establishment when aerial seeded. Dry mass of cereal rye in spring was 55–57% greater than ryegrass. Soybean and corn yield was 4 and 6% higher following ryegrass than cereal rye, respectively. Overseeded ryegrass or cereal rye after R6.5 did not affect interseeded soybean yield. Corn yields were reduced 16–33 bu acre –1 following all soybean cover crop overseeded timings.